The value of using classroom observations as part of a multi-methodological approach to evaluate student engagement in vocational agricultural education. Issue 1 (17th February 2020) - Cunningham, Kevin; Gorman, Monica; Maher, James
ABSTRACT: This paper discusses the value of using classroom observations as part of a multi-methodological approach to understand what influences student engagement in classroom settings. This action research aimed to gain insights into what influences students to participate in the classroom and was conducted in an Irish vocational agricultural college as part of an initiative aimed to enhance classroom engagement. Classroom observations were used to examine how students interact in classroom settings by observing student's behavioural engagement as the cognitive and affective domains of engagement are more difficult to observe. The findings were triangulated and validated with data from the teacher interviews, student focus groups, and a student survey. This paper details the multi-methodological approach taken, how classroom observations were developed and used, and the value they brought to evaluate what impacted student engagement within this context.